2015
DOI: 10.1016/j.plaphy.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

UV-B induction of the E3 ligase ARIADNE12 depends on CONSTITUTIVELY PHOTOMORPHOGENIC 1

Abstract: The UV-B inducible ARIADNE12 (ARI12) gene of Arabidopsis thaliana is a member of the RING-between-RING (RBR) family of E3 ubiquitin ligases for which a novel ubiquitination mechanism was identified in mammalian homologs. This RING-HECT hybrid mechanism needs a conserved cysteine which is replaced by serine in ARI12 and might affect the E3 ubiquitin ligase activity. We have shown that under photomorphogenic UV-B, ARI12 is a downstream target of the classical ultraviolet B (UV-B) UV RESISTANCE LOCUS 8 (UVR8) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…What is then the function of the PUB11-dependent ubiquitination of ALA10? Several possible functions of ubiquitin modification have already been reported in plants, from alteration of abundance to modification of localization and shift in interaction properties (Guerra and Callis, 2012;Xie et al, 2015). Here we show that PUB11 does not seem to have an impact on ALA10 abundance but rather influences ALA10 localization.…”
Section: Discussionsupporting
confidence: 53%
“…What is then the function of the PUB11-dependent ubiquitination of ALA10? Several possible functions of ubiquitin modification have already been reported in plants, from alteration of abundance to modification of localization and shift in interaction properties (Guerra and Callis, 2012;Xie et al, 2015). Here we show that PUB11 does not seem to have an impact on ALA10 abundance but rather influences ALA10 localization.…”
Section: Discussionsupporting
confidence: 53%
“…1, Kliebenstein et al (); 2, Brown et al (); 3, Brown & Jenkins (); 4, Favory et al (); 5, Brown et al (); 6, Gruber et al (); 7, Feher et al (); 8, Davey et al (); 9, Lang‐Mladek et al (); 10, Morales et al (); 11, Wargent et al (); 12, Demkura & Ballaré (); 13, Cloix et al (); 14, Huang et al (); 15, Heijde et al (); 16, Fasano et al (); 17, Tossi et al (); 18, Huang et al (); 19, Vandenbussche et al (); 20, Hayes et al (); 21, Binkert et al (); 22, Fierro et al (); 23, Mazza & Ballaré ; 24, Xie et al (); 25, Li et al (); 26, Yin et al (); 27, Tilbrook et al (); 28, Velanis et al (); 29, Heilmann et al (). 30, Hayes et al ().…”
Section: Responses Mediated By Uvr8: Integration With Other Pathwaysmentioning
confidence: 99%
“…In addition, other processes may be regulated by a combination of UV‐B pathways. Various genes, including those encoding the cyclobutane pyrimidine dimer photolyase PHR1 (Li et al ) and the E3 ubiquitin ligase ARIADNE12 (Xie et al ) are regulated by both UVR8 and non‐UVR8 pathways, depending on the spectral quality and fluence rate.…”
Section: Multiple Molecular Pathways Are Involved In Plant Responses mentioning
confidence: 99%
“…Explanations are still elusive why different action spectra are necessary for UVR8 monomerization and UV-B induced HY5 expression and whether UVR8 is the only UV-B photoreceptor or if additional factors are needed to modulate the action of UVR8 (Brown et al, 2009; Díaz-Ramos et al, 2018). UV-B responsive phenomena in mutants of uvr8 and photobiological studies indicate that UV-B signaling might also be triggered by other pathways (Ulm et al, 2004; Safrany et al, 2008; Gardner et al, 2009; Shinkle et al, 2010; Leasure et al, 2011; Lang-Mladek et al, 2012; Tilbrook et al, 2013; Xie et al, 2015; O’Hara et al, 2019). Studies also suggested that reduced pterin may be a chromophore for a putative UV-B photoreceptor (Galland and Senger, 1988; Takeda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%